Structure of an ex vivoDrosophila TOM complex determined by single-particle cryoEM - Agalya Periasamy; Pamela Ornelas; Thomas Bausewein; Naomi Mitchell; Jiamin Zhao; Leonie M. Quinn; Werner Kuehlbrandt; Jacqueline M. Gulbis (IUCrJ)
Most mitochondrial precursor proteins are encoded in the cell nucleus and synthesized on cytoplasmic ribosomes. The translocase of the outer membrane (TOM) is the main protein-import pore of mitochondria, recognizing nascent precursors of mitochondrially targeted proteins and transferring them across the outer membrane. A 3.3 Å resolution map and molecular model of a TOM complex from Drosophila melanogaster, obtained by single-particle electron cryomicroscopy, is presented. As the first reported structure of a transgenic protein expressed and purified ex vivo from Drosophila, the method provides impetus for parallel structural and genetic analyses of protein complexes linked to human pathology. The core TOM complex extracted from native membranes of the D. melanogaster retina contains transgenic Tom40 co-assembled with four endogenous TOM components: Tom22, Tom5, Tom6 and Tom7. The Drosophila TOM structure presented here shows that the human and Drosophila TOM are very similar, with small conformational changes at two subunit interfaces attributable to variation in lipid-binding residues. The new structure provides an opportunity to pinpoint general features that differentiate the TOM structures of higher and unicellular eukaryotes. While the quaternary fold of the assembly is retained, local nuances of structural elements implicated in precursor import are indicative of subtle evolutionary change.